2009
DOI: 10.1002/chem.200900279
|View full text |Cite
|
Sign up to set email alerts
|

2,6,8‐Trisubstituted 3‐Hydroxychromone Derivatives as Fluorophores for Live‐Cell Imaging

Abstract: We present the synthesis and photophysical characterisation of a series of structurally diverse, fluorescent 2,6,8-trisubstituted 3-hydroxychromone derivatives with high fluorescence quantum yields and molar extinction coefficients. Two of these derivatives (9 and 10 a) have been studied as fluorophores for cellular imaging in HeLa cells and show excellent permeability and promising fluorescence properties in a cellular environment. In addition, we have demonstrated by photophysical characterisation of 3-isobu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…5,22,23 3-Hydroxychromone (3HC) derivatives show exceptional solvatochromism of their dual emission, 24,25 due to an Excited-State Intramolecular Proton Transfer (ESIPT), but suffer from poor photostability. 26 This class of dyes found a variety of applications for probing biomembranes and protein interactions as well as for cellular imaging, 7,10,[27][28][29] and so we were particularly interested to design photostable fluorescent dyes based on these chromophores. It has been shown that the nature of photodegradation of 3HCs is photo-oxidation 26 and/or re-arrangement 30 in the tautomer state (T*) of the dye, which is an ESIPT product of the normal S1 excited state (N*).…”
Section: Introductionmentioning
confidence: 99%
“…5,22,23 3-Hydroxychromone (3HC) derivatives show exceptional solvatochromism of their dual emission, 24,25 due to an Excited-State Intramolecular Proton Transfer (ESIPT), but suffer from poor photostability. 26 This class of dyes found a variety of applications for probing biomembranes and protein interactions as well as for cellular imaging, 7,10,[27][28][29] and so we were particularly interested to design photostable fluorescent dyes based on these chromophores. It has been shown that the nature of photodegradation of 3HCs is photo-oxidation 26 and/or re-arrangement 30 in the tautomer state (T*) of the dye, which is an ESIPT product of the normal S1 excited state (N*).…”
Section: Introductionmentioning
confidence: 99%
“…Various dihalogenated chalcones have been of interest as intermediates in the synthesis of flavones and chromones 23 , 24 . Halogenated chalcones ( II–X , Figure 1 ) have been reported to exhibit high cytotoxic activity 25–28 .…”
Section: Introductionmentioning
confidence: 99%
“…Many natural products containing the flavone and isoflavone scaffolds have been reported to exhibit fluorescence, albeit with low fluorescence quantum yields. ,− Efforts have therefore focused on the development of chromone-derived fluorescent scaffolds with improved fluorescence. Luthman and co-workers demonstrated that 3-hydroxyflavone-derived fluorophores with improved fluorescence quantum yield could be used in various applications (Φ = 0.48 in EtOH) .…”
Section: Introductionmentioning
confidence: 99%
“…Many natural products containing the flavone and isoflavone scaffolds have been reported to exhibit fluorescence, albeit with low fluorescence quantum yields. ,− Efforts have therefore focused on the development of chromone-derived fluorescent scaffolds with improved fluorescence. Luthman and co-workers demonstrated that 3-hydroxyflavone-derived fluorophores with improved fluorescence quantum yield could be used in various applications (Φ = 0.48 in EtOH) . Our group have a long-standing interest in this area, and we recently described the development of a new fluorescent moiety, 3-alkyl-6-methoxy-7-hydroxy-chromone (AMHC), which exhibited a medium fluorescence quantum yield (Φ = 0.48 in 0.1 M Tris–HCl buffer, pH 8.0) starting from the readily available natural product 7-hydroxyisoflavone (Figure ).…”
Section: Introductionmentioning
confidence: 99%